Effective Strategy to Reduce Infant Mortality Rates through Neonatal Death Rate (NDR) - Harjanti, Harjanti; Novita, Risma Ayu (Universitas Muhammadiyah Sidoarjo, 2024)
Infant Mortality Rate (IMR) is an important indicator of a country's level of social welfare and public health status. The target of the Sustainable Development Goals (SDGS) in 2030 is to end with the aim of reducing neonatal mortality to 12 per 1000 live births. The results of the calculation of neonatal mortality rates at RSUD dr. Soeroto Ngawi exceed the SDGS tolerance limit of 32 per 1000 live births. The purpose of the study was to analyze strategies to reduce the Neonatal Death Rate (NDR) by classifying it based on age characteristics, birth weight and diagnosis of cause of death. The type of research is descriptive quantitative, which will describe the neonatal mortality rate with a retrospective study approach. Total sampling technique with a sample of 47 medical record documents of newborn patients aged 0-28 days. The neonatal mortality rate obtained results of 48 per 1000 live births for 1 year. The proportion of neonatal mortality with the highest in age characteristics is 0-7 days of age, which is 39 (82.97%) cases, normal weight (2,500-4,000 grams) there are 17 (36.17%) cases, and the diagnosis of the cause of death there are 30 (63.84%) cases caused by Low Birth Weight (LBW). It can be concluded based on the characteristics of the main cause of NDR, namely LBW which occurs in premature and dysmastur babies. Strategies that can be carried out are routine antenatal care examinations, screening of newborns, basic emergency obstetric neonatal services, provision of hypno breastfeending therapy and mother kangaroo mother care, provision of exclusive breastfeeding.